Critical Thinking in Social Work Training - Belchior-Rocha, H.; Casquilho-Martins, I. (Empathy Study, 2019)
It is the look at the that leads us to questioning and the answers guide us to updating and the production of knowledge. There is always, in the debates of social work professionals, the question of the search for an intervention project that gives a new meaning to the profession in order to respond, not only theoretically coherent but also efficiently, to the demands placed upon them. The purpose of this chapter is to highlight the importance of critical thinking in the training of social workers. The research is based on an exploratory study carried out with recently graduated university students, whose results point to the benefits of this soft skill in the ability to analyze, understand interactions, detect inconsistencies, systematic problem-solving, reflect on beliefs and values, and reintegrate information as a whole.